2008
DOI: 10.1038/oby.2008.251
|View full text |Cite
|
Sign up to set email alerts
|

Substantial Changes in Epicardial Fat Thickness After Weight Loss in Severely Obese Subjects

Abstract: We sought to evaluate the effect of weight loss on echocardiographic epicardial fat thickness, as index of visceral adiposity, and whether epicardial fat change after the weight loss can be proportionally different from overall body weight changes and related to cardiac parameters changes in severely obese subjects. This was an interventional study in 20 severely obese subjects (12 women, 8 men, BMI 45 ± 5 kg/m 2 , 35 ± 10 years) who underwent 6-month very low calorie diet weight loss program. Baseline and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
166
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(175 citation statements)
references
References 26 publications
6
166
2
1
Order By: Relevance
“…The results of other large studies have revealed that the degree of coronary calcification correlates with the amount of pericardial fat, and that this correlation predicts progression of atherosclerosis in subjects with low calcification followed from the outset 7 . Increased number of macrophages, T-lymphocytes and mast cells in epicardial fat but not in SAT have been demonstrated in patients with coronary artery disease by several researchers independently 8,9 and regression of epicardial fat has been observed in relation to weight reduction 10 , exercise 11 or following administration of either atorvastatin 12 or ezetimibe 13 . Whether this reduction leads to a decreased cardiovascular risk remains unclear and needs to be further examined.…”
Section: Fat Depots: Perivascular Epicardial Visceral and Subcutaneousmentioning
confidence: 99%
“…The results of other large studies have revealed that the degree of coronary calcification correlates with the amount of pericardial fat, and that this correlation predicts progression of atherosclerosis in subjects with low calcification followed from the outset 7 . Increased number of macrophages, T-lymphocytes and mast cells in epicardial fat but not in SAT have been demonstrated in patients with coronary artery disease by several researchers independently 8,9 and regression of epicardial fat has been observed in relation to weight reduction 10 , exercise 11 or following administration of either atorvastatin 12 or ezetimibe 13 . Whether this reduction leads to a decreased cardiovascular risk remains unclear and needs to be further examined.…”
Section: Fat Depots: Perivascular Epicardial Visceral and Subcutaneousmentioning
confidence: 99%
“…Weight loss by caloric restriction, 37 exercise, 38 or bariatric surgery 39 in obese patients leads to significant reductions (9%-32%) in epicardial fat thickness. Pharmaceutical treatments associated with thinner epicardial fat target either lipid metabolism or glucose homeostasis.…”
Section: Conclusion: Therapeutic Implications and Future Directionsmentioning
confidence: 99%
“…Weight loss has been Epicardial Adipose Tissue in AF Patients shown to lead to marked reductions in pericardial fat and may limit the potentially adverse effects of pericardial fat deposits, including changes in cardiac morphology and function. 13 The effects of some pharmacological therapy on EAT have been evaluated. A recent study showed that treatment with pioglitazone in type 2 diabetic patients with CAD was associated with a reduction in inflammation-related gene expression in EAT.…”
Section: Article P 2748mentioning
confidence: 99%